Prophylactic cranial irradiation in SCLC - Suwinski, Rafal (Transl Lung Cancer Res, 2021)
Prophylactic cranial irradiation (PCI) has well established place in therapy for patients with limited-disease small cell lung cancer who responded to treatment. The data from randomized trials document that PCI reduces brain metastases rate from approximately 60% to 30%, and increases 3-year overall survival by approximately 5%. Currently, the dose of 25 Gy in 10 fractions is considered as standard. In attempt to reduce neuropsychological sequelae attributable to PCI hippocampal sparing techniques are employed. The existing studies suggest the benefit of hippocampal sparing in limiting memory and higher neurocognitive function losses, but with a risk of failures in the spared region. Ongoing studies will further validate the role of hippocampal sparing, both in terms of toxicity reduction and metastases prevention. PCI for patients who have undergone resection for stage I small cell lung cancer (SCLC) is not recommended, PCI may be, however, associated with a favourable outcome in SCLC patients who have undergone complete surgery in stages II−III. The role of PCI in extensive-disease (ED) SCLC has been evolving. Most recent evidence indicate that PCI is controversial in ED patients with response to initial chemotherapy and absence of brain metastases confirmed by contrast-enhanced MRI. The patients who do not receive PCI, must, however, receive periodic MRI examination during follow-up, i.e., remain under active surveillance with access to radiotherapy at brain relapse. The assessment of safety and effectiveness of hippocampal-sparing PCI, with or without drug neuroprotection in consideration of diverse combinations of radiotherapy, chemotherapy and immunotherapy create a background for future directions of research.